Burrhus Frederick Skinner (1904-1990): A life - Daniel W Bjork (HarperCollins, 1993)
The book is a riveting portrait of a controversial "social inventor" and entrepreneur whose ideas transformed education, child rearing, and even community life. The book explores how the conflict between Skinner's turn-of-the-century small-town upbringing and his avant-garde, intellectual education shaped his science and his ideas about its application